Handbook of Hinduism in Europe - Jacobsen, Knut A., 1956-; Sardella, Ferdinando (Handbook of oriental studies. South Asia, 2020)
"Handbook of Hinduism in Europe portrays and analyses how Hindu traditions have expanded across the continent, and presents the main Hindu communities, religious groups, forms, practices and teachings. The Handbook does this in two parts, Part One covers historical and thematic topics which are of importance for understanding Hinduism in Europe as a whole and Part Two has chapters on Hindu traditions in every country in Europe. Hindu traditions have a long history of interaction with Europe, but the developments during the last fifty years represent a new phase. Globalization and increased ease of communication have led to the presence of a great plurality of Hindu traditions. Hinduism has become one of the major religions in Europe and is present in every country of the continent"--